2005
DOI: 10.1002/jbm.a.30343
|View full text |Cite
|
Sign up to set email alerts
|

Combined chondrocyte–copolymer implantation with slow release of basic fibroblast growth factor for tissue engineering an auricular cartilage construct

Abstract: Basic fibroblast growth factor (b-FGF) may have a role in tissue-engineered chondrogenesis. However, when applied in solution, b-FGF rapidly diffuses from the implant site. In another approach for tissue engineering, poly-lactide-based copolymers have shown promise as scaffolds for chondrocytes used to tissue engineer auricular cartilage in the shape of an ear. This study evaluated the effectiveness of b-FGF impregnated in gelatin microspheres to achieve slow growth factor release for augmenting the in vivo ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
55
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 43 publications
(43 reference statements)
1
55
0
Order By: Relevance
“…Several previous studies have reported on how bFGF bonds to GMS and is slowly released from GMS (19)(20)(21)(22). We obtained bFGF impregnated-GMS through the same method described in these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported on how bFGF bonds to GMS and is slowly released from GMS (19)(20)(21)(22). We obtained bFGF impregnated-GMS through the same method described in these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Natural materials include gelatin [31,32], collagen [33], fibrin [34], heparin [35] and alginate. [36] Synthetic matrices have been generated from poly(ethylene glycol)-g-poly(lactic acid) [37], poly(lactic acid) [38], poly(lactic-co-glycolic acid) [39,40], and methylidene malonate polymers. [41] From a mechanical perspective, these scaffolds have ranged from relatively weak materials (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Isogai et al developed a composite scaffold to fabricate a complicated 3D engineered auricular cartilage with a slow-release b-FGF system. 29,41,42 From *50 to 80 mg/cm 3 b-FGF had been impregnated onto gelatin sponges. The enhanced vascular networks 41 induced by slow-release b-FGF and the proliferated chondrocytes are involved in enhanced chondrogenesis and production of extracellular matrix in cartilage regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…b-FGF-impregnated gelatin microspheres with slow release enhanced chondrogenesis in in situ engineered cartilage. 29,30 The relationship between the amount of regenerative cartilage that forms and the amount of b-FGF impregnated in gelatin microspheres has not been clarified. This study investigated the optimal amount of b-FGF with gelatin sponges to fabricate engineered cartilage.…”
mentioning
confidence: 99%
See 1 more Smart Citation